2006
DOI: 10.1007/bf03174687
|View full text |Cite
|
Sign up to set email alerts
|

The impact of a standards-based science course for preservice elementary teachers on teacher attitudes toward science teaching

Abstract: This study reports on the measured change in the attitude of students toward teaching science as a result of their experiences in an elementary activity-based science course for preservice elementary teachers. Overall, the students in this study showed a positive shift in attitude as measured by the Revised Science Attitude Scale instrument that was administered at the beginning and the end of the semester. When the researchers looked at specific subscales within the instrument, one of the four subscales did n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…Our findings provide support for claims that teacher preparation programs must provide handson experiences that promote positive attitudes toward science (Marcuccio & Marshall, 1993;Glass, Aiuto, & Andersen, 1993). Also these findings are consistent with rearch on interest and attitudes (Palmer, 2004(Palmer, :2009Minger & Simpson, 2006), and motivation theory (Glasser, 1998). Clearly, playful hands-on science activities fostered their interest, curiosity and participation in science activities.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings provide support for claims that teacher preparation programs must provide handson experiences that promote positive attitudes toward science (Marcuccio & Marshall, 1993;Glass, Aiuto, & Andersen, 1993). Also these findings are consistent with rearch on interest and attitudes (Palmer, 2004(Palmer, :2009Minger & Simpson, 2006), and motivation theory (Glasser, 1998). Clearly, playful hands-on science activities fostered their interest, curiosity and participation in science activities.…”
Section: Conclusion and Discussionsupporting
confidence: 86%
“…Jarrett and Burnley (2007; in research with geology students and faculty noted that the role of play/fun in early learning helped create interest in science. Minger and Simpson (2006) found that in an activity-based methods course preservice teachers' attitudes toward science changed in positive way. In another study, Palmer (2002) found that preservice teachers who observed children at an interactive science center recognized the importance of hands-on science teaching and the value of making science fun.…”
mentioning
confidence: 95%
“…It is believed that teachers bring with them what they have been experiencing and they shape their instructional behaviours and the quality of their science instruction according to their own experiences (Huinker & Madison, 1997;Koballa & Crawley, 1985;Lee & Krapfl, 2002;Li, 1999;Osborne, Simon, & Collins, 2003). Thus, according to Minger and Simpson (2006) and Palmer (2001), teachers' attitudes, beliefs, and behaviours about science teaching are affected by teacher education programmes. When pre-service teachers become in-service teachers, in addition to the negative or positive beliefs and attitudes they hold, they also face problems at the school and classroom level and have to adjust to the complexities of a daily teaching load and at the same time trying to develop their own self-image as a teacher.…”
Section: Introductionmentioning
confidence: 94%
“…Students had a better appreciation for the attributes necessary to be successful in science, and they had a better understanding of how science is relevant to their future careers as teachers. Recently, Minger & Simpson (2006) reported a positive shift in attitude toward science as measured by the Revised Science Attitude Scale Instrument developed by Thompson & Shrigley (1986). They conducted their study in a blended science content and pedagogy course required of all pre-service elementary teachers.…”
Section: Attitudes Toward Sciencementioning
confidence: 99%